Plant location decisions and land- use restrictions: The Turkish case - Arasıler Ünal, Ayda (My University, 2001)
Genellikle, fabrika yer seçimi için işçi, hammadde, Pazar ve ulaşım gibi temel yerseçimi kriterlerinin dikkate alındığını, çevre ve imar'la ilgili arazi kullanımı yasal kısıtlayıcılarının dikkate alınmadığını, bundan dolayı da inşaatların durdurulması, yapı izinlerinin kaldırılması ve yapının yıkımı gibi büyük zararlara uğranıldığını göstermektedir. Tez Yerseçimi modelleri uygulanırken bu modeller içerisinde sözkonusu yasal kısıtlayıcıların nasıl yer alacağını göstermek üzere hazırlanmıştır. Tezin giriş ve amaç bölümünde, tezin amacı, kapsamı, inceleme yöntemi ve çalışmaya olan gereksinim ortaya konmuştur. Tez'in nde sanayi yerseçimi yapılırken dikkate alınan faktörler ve modeller, kullanılan teorik temellere göre incelenmiştir. Tez'in Tez Çalışmalarını içeren bölümünde önce, sanayide arazi kullanımını belirleyen düzenleyici idari tasarruflar olarak planlar incelenmiştir. Daha sonra, planı bulunmayan alanlarda imar düzeni ve sanayi yer seçimi için yasal arazi kullanım kısıtlamaları çeşitli yasa, tüzük ve yönetmelikler taranarak belirlenmiştir. Tez'in sonuç bölümünde, İki Aşamalı Sanayi Yer Seçimi Modeli uygulanmıştır. Tez'in Tartışma ve Değerlendirme bölümünde ise arazi kullanımının yasal kısıtlayıcılarının kültür ve tabiat varlıklarının korunmasındaki önemi belirtilmiş, ancak, sürdürülebilir kalkınma ışığı altında bu kısıtlayıcıların belirli bir ölçüde yumuşatılmasının, ekonomik kalkınma ve çevre koruma dengesini sağlamak için çok önemli olduğu belirtilmiştir.

PLANT LOCATION DECISIONS AND LAND- USE RESTRICTIONS: THE TURKISH CASE Observations have shown that while deciding for a plant location some basic factors such as worker, raw material, market and transportation have only been taken into account, but the legal land- use restrictions which are connected with reconstruction activities and environmental protection, have not. Because of this, some investors have been faced such troubles as the removal of their building permissions, have to stop the construction of the plants, and in some cases, the demolition of the plants by court decisions. In Part I. Introduction and Objectives section of the Thesis; the aim of the study, its coverage, investigation method and the need for the study had been discussed. In Part II. General Background section of the Thesis; theoretical basis of the subject had been reviewed. The basic plant location factors and location models had been investigated with relation to theoretical approaches. In Part III of the Thesis land-use restrictions for industrial location decisions had been searched within the Turkish Laws and Regulations. In Part IV. Results section of the thesis, it was indicated that just the use of basic economic factors and models to choose the optimum plant location is not enough, therefore, Two-Level Plant Location Model should be used. In the Part V. Discussions and Evaluations section of the Thesis ; the importance of legal land-use restrictions in respect to cultural and environmental protection had been explained, but also, in respect to sustainable development principles, an equilibrium between economic development and cultural and environmental protection should be taken into account and therefore some softer measures in land-use restrictions had been suggested.
Keywords: Arazi Kullanımı; İşletmeler-çalışma Yerleri